THE INFLUENCE OF PRICE AND PRODUCT QUALITY ON IPHONE PURCHASE DECISIONS IPHONE IN THE CITY OF SURABAYA - Aufa Izzuddin Baihaqi (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
Abstract The number of smartphone products that enter the market for sale today makes consumers make several considerations when choosing a smartphone. One of them is to think about practicality in carrying out daily activities using the smartphone. The purpose of this study was to determine the effect of price and product quality variables on purchasing decisions for iphone products in the city of Surabaya. The research method is to use a quantitative approach. The research conducted by the researcher refers to the use and measurement of the linkert scale which is calculated from 1 to 5. The number of samples used is 104 samples. The data analysis test used in this study refers to the multiple linear regression test. Based on the results of research that has been carried out by researchers, there are several conclusions. First, the results of this study have shown that there is a positive and significant influence between the price variables on purchasing decisions. Second, the product quality variable has a positive and significant influence on the purchasing decision variables. The three variables of price and product quality simultaneously have a positive and significant influence on the purchasing decision variables. Keywords: Price, Product Quality, and Purchase Decision